Alcohol consumption and alcohol counselling behaviour among US medical students: cohort study. (7th November 2008) - Frank, Erica; Elon, Lisa; Naimi, Timothy; Brewer, Robert
Abstract : Objective To determine which factors affect alcohol counselling practices among medical students. Design Cohort study. Setting Nationally representative medical schools (n=16) in the United States. Participants Medical students who graduated in 2003. Interventions Questionnaires were completed (response rate 83%) at the start of students' first year (n=1846/2080), entrance to wards (typically during the third year of training) (n=1630/1982), and their final (fourth) year (n=1469/1901). Main outcome measures Previously validated questions on alcohol consumption and counselling. Results 78% (3777/4847) of medical students reported drinking in the past month, and a third (1668/ 4847) drank excessively; these proportions changed little over time. The proportion of those who believed alcohol counselling was highly relevant to care of patients was higher at entrance to wards (61%; 919/1516) than in final year students (46%; 606/1329). Although students intending to enter primary care were more likely to believe alcohol counselling was highly relevant, only 28% of final year students (391/1393) reported usually or always talking to their general medical patients about their alcohol consumption. Excessive drinkers were somewhat less likely than others to counsel patients or to think it relevant to do so. In multivariate models, extensive training in alcohol counselling doubled the frequency of reporting that alcohol counselling would be clinically relevant (odds ratio 2.3, 95% confidence interval 1.6 to 3.3) and of reporting doing counselling (2.2, 1.5 to 3.3). Conclusions Excessive drinking and binge drinking among US medical students is common, though somewhat less prevalent than among comparably aged adults in the US general population. Few students usually discussed alcohol use with patients, but greater training and confidence about alcohol counselling predicted both practising and believing in the relevance of alcohol counselling. Medical schools should consider routinely training students to screen and counsel patients for alcohol misuse and consider discouraging excessive drinking.